Effectiveness of Amino Alcohol-Based Surface-Applied Corrosion İnhibitors in Chloride-Contaminated Concrete - Söylev, Tayfun Altuğ; McNally, Ciaran; Richardson, Mark (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2007)
In the present study, the effectiveness of two generations of amino alcohol (AMA) based surface-applied corrosion inhibitors (SACI) is investigated. The inhibitors were applied on the surface of the hardened concrete. The results showed that the new generation of the SACIs was effective in keeping the corrosion rate low compared to the control samples despite high chloride content at the level of the embedded steel and the effectiveness increased with chloride concentration. However none of the inhibitors were effective when they were applied after the initiation of corrosion. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Corrosion; Durability; Chloride; Admixture; İnhibitor; Reinforced-Concrete; Steel; Korozyon; Dayanıklılık; Klorid; Karışım; Önleyici; Betonarme; Çelik